Implementasi Program Home Visit Dalam Pembentukan Karakter Disiplin Siswa di SMP Negeri 6 Taliwang - Agit Mirsya, M.; Sumardi, Lalu; Kurniawansyah, Edy; Pandapotan Simaremare, Tohap (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2024)
This research examines the implementation of the home visit program in the formation of student discipline character in SMP Negeri 6 Taliwang. The purpose of this research is to know the implementation of home visit program in SMP Negeri 6 Taliwang and to know the impact of home visit program implementation in discipline character building. This research uses a qualitative approach with the type of case study research. Data collection techniques used interviews, observation, and documentation. The result of this research shows the implementation process of home visit program in shaping students' discipline character in SMP Negeri 6 Taliwang and the impact of home visit program implementation on shaping students' discipline character in SMP Negeri 6 Taliwang. There are 3 stages of the home visit program implementation process, namely planning, implementation and evaluation. Based on this process, the impact of the home visit program was obtained in the form of an increase in students' disciplinary attitudes in class, an increase in the discipline of student attendance and an increase in the attitude of obeying the rules at school. Based on these results, the implementation of the home visit program can shape the discipline character of SMP Negeri 6 Taliwang students.